The Effect of Lifestyle, Brand Image, and Product Quality on iphone Purchase Decisions - Mariah Mariah; Yuswari Nur (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This study aims to determine the effect of lifestyle, brand image, and product quality on iPhone purchasing decisions for students who use iPhones at the Indonesian Nobel Institute of Technology and Business. The population used in this study were all Indonesian Nobel Institute of Technology and Business students who used the iPhone, with a sample of 96 respondents. The sampling technique is a non-probability sampling technique, namely convenience sampling. Data collection was carried out using a questionnaire technique. The data analysis method used is multiple linear regression analysis techniques, classic assumption test, F test, t-test, and coefficient of determination. The results of this study indicate that brand image, product quality, and lifestyle simultaneously influence Iphone purchasing decisions. Brand image and lifestyle have a partial effect on iPhone purchasing decisions.